Management of Frontal Bone Fractures. Issue 7 (October 2019) - Schultz, Jerette J.; Chen, Jeffrey; Sabharwal, Samir; Halsey, Jordan N.; Hoppe, Ian C.; Lee, Edward S.; Granick, Mark S.
Abstract : Background: The purpose of this study was to examine a level 1 trauma center's 12-year experience treating frontal sinus fractures with regards to patient demographics, management strategies, and treatment outcomes. Methods: An institutional review board-approved retrospective review of all facial fractures at a level 1 trauma center was performed for the years 2000 to 2012. Patient demographics, location of fractures, concomitant injuries, use of antibiotics, surgical management strategies and outcomes were collected for all frontal sinus fractures. A significance value of 5% was used. Results: There were 291 frontal sinus fractures treated at our institution. The mean age of patients was 34.4 years with a male predominance (90%). The most common mechanisms of injury were assault in 82 (28.2%) and motor vehicle accidents in 80 (27.5%). Anterior table fractures were seen in 261 patients (89.7%) and posterior table fractures were seen in 181 (62.2%). Treatment included ORIF with sinus preservation in 18 (6.2%), ORIF with sinus obliteration in 20 (6.9%), and cranialization in 18 (6.2%). Antibiotics were started on admission in 152 patients (52.2%). Fatality occurred in 9.3% of patients and complications included meningitis (1%), frontal sinusitis (1%), early wound infection (0.3%), and mucopyelocele (0.3%). Conclusions: Frontal sinus fractures in our center are most often caused by interpersonal violence. Anterior table fractures were more common than posterior table fractures and ORIF with sinus obliteration was the most common surgical intervention. Most frontal sinus fractures at our institution (82%) were treated conservatively with no surgical intervention and we observed a low rate of long term complications. Abstract : Supplemental Digital Content is available in the text